Implementation Of The Death Criminal Sanction In The Corruption Criminal Action Law - Muhammad Tetuko Nadigo Putra (Corruptio, 2022)
Criminal act of corruption which is governed under, subsequent called UUTPK is not yet set assertive regarding the amount and related conditions with inner country state as specific stated under Article 2 Paragraph (2) UUTPK which states: that in case act criminal corruption like as referred to in paragraph (1) is carried out in situation-specific, then criminal dead could implement. The method study used in this paper are juridical normative and empirical. Approach the study was conducted at the Tanjung Karang District Court, Bandar Lampung District Attorney, Peradi Lampung DPC, and Lampung University. Type of data used is secondary data and primary data. The results of research and discussion show that death criminal sanction not applied in acts of criminal corruption as set is in UUTPK. Regulation Number 20 of 2001 contained in Article 2 paragraph (2) is inefficient because in its implementation the judge often decides to use Article 2 paragraph (1) UUTPK in case of criminal corruption because provision chapter clearly explains the terms and the conditions of the quert article. This provision chapter could be applied, and P 2 paragraph (2) the original has much weakness because Article 2 paragraph (2) do not explain the apparent size and terms subjugated on somebody for convicted death sanction according to the author. If Article being (2) paragraph 2 wants to be applied, it must be clarified in the chapter/provision. For example, if corruption or loss of state money is above Rp. 1 billion, the convict must be punished dead. The reason as to why death criminal sunction is not applied effectively wittin corruption criminal act , has also something to do with the willingness of Indonesian judges to conviet perpetraturs with maximum punishment, of course in the and such legal decision must also be seen from varius aspects